Effect of construction of TiO2 nanotubes on platelet behaviors: Structure-property relationships. (15th March 2017) - Huang, Qiaoling; Yang, Yun; Zheng, Dajiang; Song, Ran; Zhang, Yanmei; Jiang, Pinliang; Vogler, Erwin A.; Lin, Changjian
Graphical abstract: Abstract: Blood compatibility of TiO2 nanotubes (TNTs) has been assessed in rabbit platelet-rich plasma (PRP), which combines activation of both blood plasma coagulation and platelets. We find that (i) amorphous TiO2 nanotubes (TNTs) with relatively larger outer diameters led to reduced platelet adhesion/activation, (ii) TNTs with relatively smaller outer diameters in a predominately rutile phase also inhibited platelet adhesion and activation, and (iii) a pervasive fibrin network formed on larger outer diameter TNTs in a predominately anatase phase. Thus, this study suggests that combined effect of crystalline phase and surface chemistry controls blood-contact behavior of TNTs. A more comprehensive mechanism is proposed for understanding hemocompatibility of TiO2 which might prove helpful as a guide to prospective design of TiO2 -based biomaterials. Statement of Significance: To realize optimal design and construction of biomaterials with desired properties for blood contact materials, a comprehensive understanding of structure-property relationships is required. In the existing literature, TiO2 nanotube has been reported to be a good candidate for biomedical applications. However, it is noticeable that the blood compatibility of TiO2 nanotubes (TNTs) remains obscure or even inconsistent in the previously published works. The inconsistency could derive from different research protocols, material properties or blood sources. Thus, a thorough investigation of the effect of surface properties on blood compatibility is crucial to the development of titanium based materials. In this paper, we explored the effect of surface properties on the response of platelet-rich plasma, especially surface morphology, chemistry, wettability and crystalline phase. The results indicated that crystalline phase was a dominant factor in platelet behaviors. Reduced adhesion and activation of platelets were observed on amorphous and rutile dominated TNTs, whereas anatase dominated TNTs activated the formation of fibrin network. We further proposed a hypothetical mechanism for better understanding of how surface properties affect the response of platelet-rich plasma. Therefore, this study expands the fundamental understanding of the structure-property relationships of titanium based materials.